Satisfaction and gains perceived by nursing students with medium and high-fidelity simulation: A randomized controlled trial - Batista, Rui Carlos Negrão (2016)
BACKGROUND: The use of simulation to reproduce the experience of health care settings and its use as a strategy in the teaching of nurses has grown at an unprecedented rate. There is little scientific evidence to examine the differences in satisfaction and gains perceived by the students with the use of medium and high fidelity. OBJECTIVES: To analyse and benchmark gains and satisfaction perceived by nursing students, according to their participation in medium- and high-fidelity simulated practice. DESIGN: Randomized control trial post-test only design with control group. SETTING AND PARTICIPANTS: Students of the 4th year of the Bachelor's Degree in Nursing who performed medium and high-fidelity simulated practice in a Simulation Centre environment. METHODS: A satisfaction scale and a scale of perceived gains from the simulation were applied to the students who underwent simulated practice in a medium-fidelity environment (control group) and high-fidelity environment (experimental group). Statistical analysis was performed and a significance level of p<0.05 was established. RESULTS: Of the 85 students who participated in the study, the majority were female (92.94%), with an average age of 21.89years (SD=2.81years). Satisfaction is statistically significant in the realism dimension and overall satisfaction. In the gains perceived with the simulation there is a statistically significant difference in the dimension recognition/decision. CONCLUSION: Students are very satisfied with the realism of high-fidelity simulated practice and consider that this helps them more with recognition and decision compared with the medium-fidelity simulation.